2014
DOI: 10.1158/1055-9965.epi-14-0429
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive and Hormonal Risk Factors for Antinuclear Antibodies (ANA) in a Representative Sample of U.S. Women

Abstract: Background Autoantibodies are of growing interest in cancer research as potential biomarkers; yet the determinants of autoimmunity are not well understood. Antinuclear antibodies (ANA) are common in the general population, and are more prevalent in women and older adults. Here we examined the relationship of ANA with reproductive and hormonal factors in a representative sample of U.S. women. Methods We analyzed data on reproductive history and exogenous hormone use in relation to serum ANA in 2,037 females a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 62 publications
5
36
1
Order By: Relevance
“…In this sample restricted to middle age and older U.S. adults, ANA was not observed to increase with age in contrast to previous reports using NHANES data (14, 25). These prior analyses that showed ANA increasing with age included a broader age range covering the life course from 12-70+ years (14).…”
Section: Discussioncontrasting
confidence: 99%
“…In this sample restricted to middle age and older U.S. adults, ANA was not observed to increase with age in contrast to previous reports using NHANES data (14, 25). These prior analyses that showed ANA increasing with age included a broader age range covering the life course from 12-70+ years (14).…”
Section: Discussioncontrasting
confidence: 99%
“…The ANA prevalence observed in the U.S. study was comparable to that observed in a recently published report from Germany (5). As in other previous reports, women had higher frequencies of ANA positivity than did men in both studies (5,6,37), which could be related to reproductive and hormonal factors (38). While increasing frequency of ANA positivity with increasing age and according to gender has been reported, there are likely other factors involved.…”
Section: Indirect Immunofluorescence Antibody Techniquesupporting
confidence: 77%
“…Among the most commonly measured biomarkers of autoimmunity are antinuclear antibodies (ANA), which are traditionally assessed by indirect immunofluorescence and are a heterogeneous group of autoantibodies targeting both nuclear and cytoplasmic components of cells ( Tan 1989 ). Although ANA are associated with a number of autoimmune diseases, they can also develop in apparently healthy individuals after infections or following the use of medications; furthermore, their prevalence tends to be higher in parous females and the elderly ( Hollingsworth et al 1996 ; Parks et al 2014 ; Satoh et al 2007 , 2012 ). Many persistent organic pollutants (POPs) exhibit hormone-disruption properties that could lead to increased ANA, and exposure to POPs has been hypothesized to increase the risk of systemic lupus erythematosus ( Cooper et al 1998 ).…”
Section: Introductionmentioning
confidence: 99%